Engineering Solutions in Industry : Selected, Peer Reviewed Papers from the 2014 2nd International Conference on Applied Mechatronics and Android Robotics (ICAMAR 2014), August 16-17, 2014, Kuala Lumpur, Malaysia - Shu, Ming-Hung (Applied mechanics and materials ;, 2014)
Collection of selected, peer reviewed papers from the 2014 2 nd International Conference on Applied Mechatronics and Android Robotics (ICAMAR2014), August 16-17, 2014, Kuala Lumpur, Malaysia. The 55 papers are grouped as follows: Chapter 1: Designing in Mechanical Engineering, Chapter 2: Technologies and Instruments for Measurements, Chapter 3: Mechatronics, Robotics and Control, Chapter 4: Power Engineering, Electrical Machines and Apparatus, Chapter 5: Technologies in Construction, Chapter 6: Information Technologies, Data Processing and Networks, Chapter 7: Production Management.